129 Genomic Relationship Between PRRSV Wild-type Infection and PRRSV Vaccination for Antibody Response and Reproductive Performance. (7th May 2021) - Sanglard, Leticia P; Hickmann, Felipe; Huang, Yijian; Gray, Kent A; Linhares, Daniel; Dekkers, Jack C; niederwerder, Megan; Fernando, Rohan; Serão, Nick V
Abstract: Immunoglobulin G antibody response, measured as sample-to-positive (S/P) ratio, to Porcine Reproductive and Respiratory Syndrome virus (PRRSV) has been proposed as an indicator trait for improved reproductive performance in PRRSV-infected purebred sows and PRRSV-vaccinated crossbred gilts. In this study, we investigated the genetic correlations (rg ) of S/P ratio following a PRRSV outbreak and PRRSV-vaccination with performance in non-exposed and PRRSV-exposed sows. PRRSV outbreak phase was defined based on previously described methodologies after the detection of typical clinical signs of PRRSV infection. 541 Landrace sows had S/P ratio measured at ~54 days after the beginning of the PRRSV outbreak (S/Poutbreak ), and 906 Landrace x Large White naïve F1 gilts had S/P ratio measured at ~50 days after vaccination with a commercial modified live PRRSV vaccine (S/PVx ). 711 and 428 Landrace sows had reproductive performance recorded before and during the PRRSV outbreak, respectively. 811 vaccinated F1 animals had farrowing performance for up to 3 parities. All animals were genotyped for ~28K SNPs. The estimate of rg of S/Poutbreak with S/PVx was high (rg ±SE = 0.72±0.18). Estimates of rg of S/Poutbreak with reproductive performance in F1 sows were low to moderate, ranging from 0.05±0.23 (number stillborn) to 0.30±0.20 (total number born). Estimates of rg of S/PVx with reproductive performance in non-infected purebred sows were moderate and favorable with number born alive (0.50±0.23), but low (0 to -0.11±0.23) with litter mortality traits. Estimates of rg of S/PVx were moderate and negative (-0.47±0.18) with the number of mummies in PRRSV-infected purebred sows and low with other traits (-0.29±0.18 for total number born to 0.05±0.18 for number stillborn). These results indicate that selection for antibody response following a PRRSV outbreak collected in purebred sows and to PRRSV vaccination collected in commercial crossbred gilts may increase litter size of non-infected and PRRSV-exposed purebred and commercial crossbred sows.